(untitled) (Research, Society and Development, 2021)
Some soybean cultivars of perennial cycle may show plasticity in the sprouting of the lateral branches, or even, it can be stimulated after their apical pruning in different phenological stages of the culture. Given the above, this work aimed to evaluate the development of soybean cultivars of indeterminate growth after apical pruning. The experiment was carried out in October 2019, at Faculdades Integradas Stella Maris (FISMA), located in the city of Andradina, State of São Paulo. The design was completely randomized, in a 2x4 factorial scheme, with two soybean cultivars, DM81I84 IPRO and SYN 1687 IPRO, interacting with apical pruning in four different stages of development, namely: pruning (control), V4, V8 and R2, making eight treatments and with five repetitions, totaling 40 plots or vessels. Apical pruning on soybean cultivars DM81I84 IPRO and SYN 1687 IPRO is not recommended. Apical pruning in the soybean reproductive phase has a negative influence on crop productivity. A soybean cultivar DM81I84 IPRO stood out in the production characteristics. The number of branches has a positive correlation with productivity in soybean.